Inhibition of Classical and Alternative Modes of Respiration in Candida albicans Leads to Cell Wall Remodeling and Increased Macrophage Recognition - Duvenage, Lucian (mBio, 2019)
The human fungal pathogen Candida albicans requires respiratory function for normal growth, morphogenesis, and virulence. Mitochondria therefore represent an enticing target for the development of new antifungal strategies. This possibility is bolstered by the presence of characteristics specific to fungi. However, respiration in C. albicans, as in many fungal organisms, is facilitated by redundant electron transport mechanisms, making direct inhibition a challenge. In addition, many chemicals known to target the electron transport chain are highly toxic. Here we made use of chemicals with low toxicity to efficiently inhibit respiration in C. albicans. We found that use of the nitric oxide donor sodium nitroprusside (SNP) and of the alternative oxidase inhibitor salicylhydroxamic acid (SHAM) prevents respiration and leads to a loss of viability and to cell wall rearrangements that increase the rate of uptake by macrophages in vitro and in vivo. We propose that treatment with SNP plus SHAM (SNP+SHAM) leads to transcriptional changes that drive cell wall rearrangement but which also prime cells to activate the transition to hyphal growth. In line with this, we found that pretreatment of C. albicans with SNP+SHAM led to an increase in virulence. Our data reveal strong links between respiration, cell wall remodeling, and activation of virulence factors. Our findings demonstrate that respiration in C. albicans can be efficiently inhibited with chemicals that are not damaging to the mammalian host but that we need to develop a deeper understanding of the roles of mitochondria in cellular signaling if they are to be developed successfully as a target for new antifungals.